CARACTERÍSTICAS DA APRENDIZAGEM DOCENTE EMERGENTES DO CONTEXTO DO ESTÁGIO SUPERVISIONADO EM MATEMÁTICA A PARTIR DE UM TRABALHO COLABORATIVO: A DISCALCULIA EM QUESTÃO - Porto, Eliane Quincozes (2024)
This investigation was developed in the Research Line on Teacher Training in Science and Mathematics, in the Postgraduate Program in Science and Mathematics Teaching at the Franciscan University. It aimed to identify characteristics of teaching learning, which emerge from the context of the supervised internship in Mathematics, based on collaborative work, focusing on dyscalculia. The following research actions were defined: I. Bibliographical survey aiming to identify research aimed at collaborative training in the context of dyscalculia; II. Theoretical study on the initial and continuing training of teachers in the context of supervised internship in mathematics; III. Theoretical deepening on the topic of dyscalculia; IV. Creation of a collaborative group between supervising teachers of the supervised internship and a special educator; V. Development of a collaborative activity in the supervised internship discipline between undergraduate students, Mathematics teachers and Special Education teacher; SAW. Analysis of the interactions established during the creation of the collaborative group and the development of the collaborative activity in the supervised internship discipline. The work was guided by a qualitative approach and the theoretical elements involved dialogued with the argumentative structure of Vigotski's cultural processes (2003), which conceives the social, cultural and historical environment as a source of development. Therefore, the research took place in a face-to-face training group, which emerged in the Supervised Internship subjects of the Mathematics Degree Course at the Federal Institute of Education, Science and Technology Farroupilha – Campus Júlio de Castilhos, based on a work plan prepared in a collaborative and dialogued by research participants. Data collection took place through audio recordings of the Collaborative Training Group meetings, later transcribed, and records in the field diary, as well as questionnaires with teachers and undergraduate students. As analysis procedures, we covered the principles of Discursive Textual Analysis, by Moraes and Galiazzi (2013), organized into three a priori categories: the first, Interpersonal and Intrapersonal Process; the second, Personal and Professional Trajectory and the final category, Appropriation of Knowledge, Knowledge and Practices. We conclude that this research contributes to teaching learning, in the context of dyscalculia, covering the periods of initial training and continuing training, highlighting the relevance of collaborative work in the space of the Supervised Curricular Internship for expanding perspectives in teaching mathematics for a inclusive perspective.